Sistem Informasi Pencatatan Data Pelanggan pada Telkomsel Grapari Banda Aceh - Febri Hertana (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2020)
The purpose of the research is to; 1) Generating a customer information system on Telkomsel GraPARI Banda Aceh, 2) To find out the application of the information system that has been built, and 3) Apply the system that was built using Visual Basic. This research was conducted at Telkomsel GraPARI Banda Aceh and conducted for 9 (nine) months of 2015-2016. The method used for system development, researchers use the methodology Rapid application development (RAD) and Data Flow Diagrams (DAD). This research has succeeded and completed the design of information systems for recording customer data at Telkomsel Grapari Banda Aceh, the application was built using the stages of the Rapid application development (RAD) model. The application was built using Visual BASIC and as a database using Microsoft Office Access. The application of the information system that has been built is still in the prototype and there is still a need for study and development of current technologies such as the use of mobile and cloud databases involving interconnection to make it easier for GraPARI units to connect.